2017
DOI: 10.1021/acs.jnatprod.6b00921
|View full text |Cite
|
Sign up to set email alerts
|

Characteristic α-Acid Derivatives from Humulus lupulus with Antineuroinflammatory Activities

Abstract: Twenty compounds, including 14 new α-acid derivatives, a new chromone, and five known compounds, were identified from the pistillate inflorescence of Humulus lupulus (hops), and their structures were elucidated via physical data analysis. The absolute configurations of new α-acid derivatives 1-11b were determined by comparing their computed and experimental electronic circular dichroism spectra using TDDFT and NMR spectroscopic data. A putative biosynthetic pathway for the identified components was deduced. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(32 citation statements)
references
References 27 publications
0
32
0
Order By: Relevance
“…Li et al, 2017c) or xanthohumol and a-acid derivatives such as humulones in Humulus lupulus flowers (J. Li et al, 2017b;. Nevertheless, these compounds might only be slightly different from each other in terms of skeletons as illustrated in the following example: the compounds which structures are shown in Figure 4 were recently isolated from six different species of Euphorbia.…”
Section: Zizyphus Jujubamentioning
confidence: 97%
“…Li et al, 2017c) or xanthohumol and a-acid derivatives such as humulones in Humulus lupulus flowers (J. Li et al, 2017b;. Nevertheless, these compounds might only be slightly different from each other in terms of skeletons as illustrated in the following example: the compounds which structures are shown in Figure 4 were recently isolated from six different species of Euphorbia.…”
Section: Zizyphus Jujubamentioning
confidence: 97%
“…▶ Table 3 Percentage of prenylated hops compounds (1)(2)(3)(4)(5) in investigated samples (Prod1-6) (n = 3) determined via quantitation using the PDA signal at 220 nm. The calculated recommended daily intake of reference substances in μg per dietary product (Prod1-4) is given in parentheses.…”
Section: Standards Samples and Solventsmentioning
confidence: 99%
“…Apart from this, a considerable number of pharmacological research studies has been conducted on hop strobile and its constituents regarding estrogenic activities, anticancer properties, and anti-inflammatory effects [3][4][5]. Some of these results have been…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These active ingredients may be promising resources for the development of new antineuroinflammation drugs. [19][20][21][22][23][24][25][26][27][28] A large number of natural products have shown strong anti-neuroinflammatory activities in vitro, and some of them have been demonstrated effective in animal models. For example, we reported that pterostilbene, the major component of Chinese Dragon's Blood, could reduce LPS-induced learning and memory impairment evaluated by Morris water maze and Y-maze tests.…”
Section: Introductionmentioning
confidence: 99%